The Effects of Conflict on Fertility in Rwanda - Schindler, Kati; Bruck, Tilman (2012)
The aim of this paper is to study the short and long-term fertility effects of mass violent conflict on different population sub-groups. The authors pool three nationally representative demographic and health surveys from before and after the genocide in Rwanda, identifying conflict exposure of the survivors in multiple ways. The analysis finds a robust effect of genocide on fertility, with a strong replacement effect for lost children. Having lost siblings reduces fertility only in the short term. Most interesting is the continued importance of the institution of marriage in determining fertility and in reducing fertility for the large group of widows in Rwanda.